BLENDED CURRICULUM OF VOCATIONAL HIGH SCHOOL BASED ON PESANTREN AS TOOL ONTO FORM JUVENILE CHARACTER AT URBAN AREA - Zulihi Zulihi; Ahmad Bustomi; Najmi Hidayatus Salam (Akademika : Jurnal Pemikiran Islam, 2023)
This article aims to investigate the Curriculum of Vocational High School base on pesantren as the main core of education which especially at urban area and to discover character as impact of it. It is expected that the brawl between schools in the city can be reduced. The brawler is dominated by students of vocational high school, moreover it comes up since a Youtuber explained his story on YouTube media. This is reinforced by the start of the vacuum of middle school students in studying religion. This research used a qualitative approach and the type of the research is field research. Informants in this study were Kyai, Principal, Teachers and Students. Data collection used interviews, direct observation and documentation. Data validation utilized triangulation by three of data resources and triangulation by three of data collecting technique. The data analysis used was the Miles and Huberman model. The steps were data reduction, data display, conclusion drawing and verification. The research results presented that Curriculum of Pesantren-Based Vocational High School is a combination of general curriculum of Vocational High School and Pesantren Curriculum. This consists of curriculum objectives that students are able to master General Science as well as Religious Science. Second, the content / subject is in the form of vocational lessons and kitab kuning. Third, the teaching method uses bandongan, lecture, question and answer and practice methods. Fourth, the organizations that play a role are all stakeholders of schools and Islamic boarding schools. Fifth, evaluation is carried out in teacher meeting forums, teacher personal evaluations and meetings between teachers and Kyai. Sixth, the characters formed consist of religious, tolerance, discipline, National spirit and Love of homeland, tolerance, social caring and Friendly/communicative.